New taxa in Maerua, Capparaceae, proposed for the Flora of Ethiopia / L. E. Kers - Kers, Lars e. (2007)
During studies of Capparaceae carried out for the Flora of Ethiopia, the following new taxa in Maerua were discovered
il byn
Keywords: Capparaceae